The fifteenth century : the prospect of Europe - Aston, Margaret, 1932-2014 ([History of European civilization library], 1968)
The theme of this study of the 15th century is the emergence of Europe as an entity. It was a period of discovery and questioning: a watershed in European history which is all too often glossed over with the catchword Renaissance. Here the Renaissance is seen as part of a larger context - religious, social, cultural and economic. The great events of the century were the plague, the capture of Constantinople by the Turks, the invention of the printing press, the exploration of the world and the revival of classical studies.